Identification of Public Green Open Space in The Merdeka Square Area of Binjai City: Social Reality Architecture - Deni, Deni; Heria Lestari, Wanda; Muliana, Erna; Nasruddin, Nasruddin (International Journal of Engineering, Science and Information Technology, 2022)
Urban Green Open Space has important benefits for the lives of its residents. However, the problem that often arises is that there are many green open spaces in the city only as spaces that are responsive to the climate, environment, and as noise absorbers. Even though its existence is more than that, Green Open Space should also be able to fulfill the social activities of city dwellers in interacting, communicating and other social realities to create positive mental growth for fellow city residents. Architecture can be used as a vehicle to make a place not only a visual use but also can be a benefit for human life in the quality of its social reality. Therefore, research activities are needed by observing the relationship between Green Open Space and social activities of the city community as users to find the identity of the place so that the character is seen as the cause of the place to exist. The research was conducted by adopting a qualitative method that was translated descriptively at certain times in a factual manner so that the audience got a clear picture of the social reality that occurred. The results of the study explain that the pattern of activities that occur interactively on the character of the place provided contextually is intended for teenage visitors. There is no strict place limit between adolescent habitus social activities, this is a stereotype of the arena, capital, and power of adolescents who tend to be free.